New variety of “quinoa” Chenopodium quinoa Wild. (Chenopodiaceae) for the northern highlands of Peru with outstanding agronomic and commercial characteristics - Tejada Campos, Toribio Nolberto; Instituto Nacional de Innovación Agraria (2021)
In order to generate a new variety of quinoa for the northern highlands of Peru and contribute to the competitiveness of this andean grain, this research was carried out between 2013 and 2018. Phases of introduction and evaluation of germplasm, genetic improvement and advanced evaluation of promising materials were carried out. The first two phases carried out in INIA experimental fields and the third in farmer’s fields. Phenotypic characteristics, physiological maturity, mildew reaction and grain yield were evaluated. Also, there was opinion of farmers. Quantitative data was analyzed using ANVA and Duncan’s test. From the Genetic Compound A, introduced from the central highlands, the new variety of quinoa was generated, called INIA 437 Red of the North. It is accepted by the farmers of the research, It has white grain and semi-sweetness; purple in foliage and panicle; as well as outstanding characteristics of mildew tolerance and productivity, showing less damage to the disease and greater yield than the Witness, White of Junín variety; also It has greater profitability and productive stability than this; being suitable for cultivation in the study area.